Characterization of dehydrated keratin protein extracted from chicken feather using NaOH - Basma Y., Alashwal; Arun, Gupta; Mohamed Saad, Bala Husain (IOP Publishing Ltd, 2019)
Keratin is one of the most significant biomaterials through commercially available due to its relatively good biocompatibility, excellent mechanical properties, high physicochemical, and good formatting-film ability. Chicken feather is the essential waste in the poultry industries which can get and control the quality of the keratin easier than the other keratin sources that the pure keratin presents a 90% of the featherweight. Chicken feathers are abundant of keratin protein which can be considered as a suitable protein source and used as a component in the cosmetic and pharmaceutical industry. The aim of this study is using the chicken feather source to extract keratin portion. Further, the chemical structure of the compound was examined by Fourier transform infrared spectroscopy (FTIR) while surface morphology analysis was described by Scanning electron microscopy (SEM) and X- Ray Diffraction resulted the crystalline form of the chicken feather dehydrated keratin. In this work, the drying of keratin in vacuum conditions was analyzed and presented a fulfilled result.